IMPLEMENTING A WRITING WORKSHOP APPROACH WITH TRANSLANGUAGING IN TAIWANESE VOCATIONAL EFL CLASSROOMS - Novi Oky Dwi Saputra; Desi Rohayati (RADJA PUBLIKA, 2025)
Writing is a fundamental skill in language learning, yet many EFL students struggle with generating ideas, organizing sentences, and maintaining coherence. This study investigated how a Writing Workshop, combined with translanguaging strategies, could support Taiwanese vocational high school students in developing their English writing skills. Thirteen tenth-grade students participated in six 90- minute sessions on the theme “My Dream Job,” following workshop stages of mini- lesson, independent writing, peer conferring, sharing, and reflection. Translanguaging allowed students to alternate between Mandarin (L1) and English (L2) during brainstorming, drafting, and revising, helping them focus on meaning and creativity before accuracy. Data from drafts, peer feedback, observations, and reflection sheets were analyzed thematically, revealing that translanguaging promoted active participation, idea development, and confidence, while the Writing Workshop provided structure, scaffolding, and collaborative opportunities. Visual tools like thinking bubbles and illustrations enhanced comprehension, vocabulary, and engagement. Students demonstrated creativity, ownership, and confidence in expressing ideas, supported by bilingual peer discussions and teacher guidance. Overall, integrating the Writing Workshop with translanguaging created an inclusive, student-centered environment that fostered both language development and learner confidence, offering a practical framework for enhancing EFL writing in vocational classrooms.